STRUCTURE OF COSTS AND EXPENDITURES IN AGRO TECHNOLOGIES OF DIFFERENT INTENSITY LEVELS - Gostev, Andrei Valerievich; Pykhtin, Alexey Ivanovich (Journal of Applied Engineering Science, 2017)
As a result of the analysis and generalization of the obtained data average structures of prime costs and expenditures in grain crop cultivation technologies were defined. They testify the nonequivalence of the impact of different techniques on the prime costs and expenditures depending on the application of extensive, basic, and intensive agro technologies. Thus, for extensive grain cultivation technologies the most costly in terms of economy and energy expenditures is sowing, which is connected mainly with heavy seeding of most small grain crops. Therefore, the main trend in cost-effective use of resources for extensive grain crop cultivation technologies is application of resource saving elements while sowing. Another way for the cost-effective use of resources can be the reduction of used recourses during harvesting and soil preparation. Using basic grain crop cultivation technologies in addition to the already mentioned common for extensive technologies trends in resource-saving scientifically grounded use of the system of fertilizers and crop protection products can be involved; they amount to 1/3 – 1/2 of overall costs and expenditures in agro technologies of this type. In intensive agro technologies the proportion of costs of plant protection products and fertilizers further increases and the proportion of costs for sowing decreases. Therefore, the main trend in intensive grain crops cultivation is scientifically-grounded use of fertilizers and protection products. Hence, with the increase of the technology intensification level the impact of such agro technological elements as tillage, sowing and harvesting decreases. It is connected mostly with the fact that for extensive technologies these elements are the most costly ones and correspondingly, their values significantly impact the total values of the overall costs of the applied technologies. On the other hand, along with the increase of the technology intensity level the role of mineral fertilizers and plant protection products increases since these elements facilitate quantitative and qualitative improvement of the cultivated crops capacity.